THE CONCEPT OF "SELF" AND THE "OTHER" IN WESTERN MOVIES - Basuki, Ribut (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
Melodrama has been a part of the American life since colonial time. This genre, with its ’hero-villain’ or ’black and white’ development of characters, has formed the idea of the American heroes. In Western films, in which the ’local’ themes of westward movement on the American society are developed, melodrama treats the dichotomy of hero-villain more stereotypically. The heroes depict the concept of the American ’self’ and the villains picture the ’other.’ However, the development of Western film shows that the stereotypical treatment on ’self’ and the ’other’ undergoes some changes.